1997
DOI: 10.1520/jfs14116j
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Fingermark Enhancement Light Sources on Subsequent PCR-STR DNA Analysis of Fresh Bloodstains

Abstract: This paper describes a study designed to investigate the effects of light sources used to enhance fingermarks on the subsequent polymerase chain reaction (PCR)-short tandem repeat (STR) analysis of bloodstains. Dried bloodstains on glass were exposed for up to 30 min to five different light sources: Argon ion laser, Polilight UV, Polilight green, Superlite, and shortwave UV. The bloodstains were subsequently analyzed using a quadruplex PCR system. It was found that treating the bloodstains with four of the fiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
1

Year Published

1999
1999
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(17 citation statements)
references
References 8 publications
0
15
0
1
Order By: Relevance
“…A study was already performed that demonstrated that DNA typing of biological stains such as blood and saliva was not affected by the use of cyanoacrylate, gentian violet, ninhydrin or amorphous carbon [10]. Other investigations studied the influence of different (laser) lights and fingerprint enhancement light sources on DNA typing of human bloodstains [11,12]. This present study investigates the use of a variety of dactyloscopic powders before DNA typing with the STR methodology, and will differentiate between the different dactyloscopic powders used.…”
Section: Introductionmentioning
confidence: 99%
“…A study was already performed that demonstrated that DNA typing of biological stains such as blood and saliva was not affected by the use of cyanoacrylate, gentian violet, ninhydrin or amorphous carbon [10]. Other investigations studied the influence of different (laser) lights and fingerprint enhancement light sources on DNA typing of human bloodstains [11,12]. This present study investigates the use of a variety of dactyloscopic powders before DNA typing with the STR methodology, and will differentiate between the different dactyloscopic powders used.…”
Section: Introductionmentioning
confidence: 99%
“…In general, these development techniques have been shown to not harm polymerase chain reaction (PCR) based DNA testing, but as shown in Table 63.1 there are some exceptions. For example, prolonged exposure (>30 seconds) to a shortwave UV light source has been shown to harm DNA (Andersen and Bramble 1997), and if 63 Forensic DNA Analysis Physical methods Black/white powder No interference, but caution: powder will inhibit PCR and must be removed during extraction Stein et al 1996;van Oorschot et al 2003 Flame soot No interference Grubwieser et al 2003 Manoxol-molybdenum No interference Grubwieser et al 2003 Physicochemical methods Iodine and chemical fixing No interference Grubwieser et al 2003 Cyanoacrylate fuming and cyan colouring…”
Section: Evidence Collection and Preservation At The Crime Scene And mentioning
confidence: 99%
“…Another disadvantage of this technique is that certain types of radiation (i.e. ultra-violet) may cause damage to DNA present within the sample [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies have already been performed to determine the effectiveness of various spectroscopic techniques for the identification of biological fluids, including ultravioletvisible (UV-vis) [21], infrared (IR) [23][24][25] and Raman spectroscopy [26][27][28][29]. While UV radiation may damage DNA contained within a fluid sample [5,6], IR spectroscopy has proven to be an interesting means to 'fingerprint' body fluids as this technique can determine the presence of specific classes of molecules in body fluids with sample volumes as small as 10 -20 μL [23][24][25]. Nevertheless, most of the IR studies carried out so far employ benchtop instruments that cannot be taken to the crime scene.…”
Section: Introductionmentioning
confidence: 99%